Prospective teachers' proficiency in punctuation rules and opinions related to punctuation problems - BENZER, AHMET (ELSEVIER SCIENCE BV, 2010)
In this study the students in education faculties that they have problems with their punctuation perspective of these issues to determine the underlying causes, and from there to the solution of problems with recommendations for action is intended to bring. To this end, students having written essays about two specific issues were examined punctuation and then the students in terms of proficiency in punctuation, most open-ended questions about problems they face are addressed. Student responses obtained from qualitative (content analysis) can be analyzed with data analysis are interpreted. According to the study results it is found out that while the vast majority of students in practice at most have problems whether the specific words will be written adjacent or apart, they identified during the open-ended questions the answers in majority of punctuation mistakes are made in correction mark and that the reason behind incorrect usage of punctuation can be traced back to education concept. However, students stress that they know the rules regarding punctuation but don't have the using habit. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Turkish education; prospective techers; punctuation rules